ANALYSIS OF STUDENTS 'TRENDS TO OBTAIN LEARNING MOTIVATION THROUGH INDIVIDUAL COUNSELING IN CLASS IX STUDENTS OF SMP N 18 SURAKARTA STUDY YEAR 2020/2021 - Lala Putri Kusumawati; Lydia Ersta Kusumaningtyas; Eko Adi Putro (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
This study aims to determine the results of "Analysis of the Trends in Students to Obtain Learning Motivation Through Individual Counseling Services for Class IX Students of SMP Negeri 18 Surakarta Academic Year 2020/2021." The subjects of this study were students of class IX with low learning motivation, parents and counseling teachers. The object of this research is to analyze the students' tendency to learn motivation through individual counseling by discussing it in a qualitative study. The data collection techniques used in this research are observation, interview and documentation methods. The observation method is used to obtain data sources from clients during the interview. While the interview method is used to obtain information from several sources related to the tendency of students to gain learning motivation through individual counseling. While the documentation method is used to obtain activity data during the research as well as supporting data in this study. The validity of the data in this study is the triangulation of sources, triangulation of techniques. Triangulation of sources is the collection of different data using the same technique. while the triangulation of techniques is data collection by researchers using different data collection techniques to obtain data from the same source. In this study, the data analysis model of Miles and Huberman used data analysis where data analysis was carried out when data collection took place, and after completing data collection within a certain period. If the answers to the results of the interview after being analyzed are not satisfactory, the researcher will continue the questions again, until a certain stage is obtained data that is considered credible. Based on the data analysis, the conclusion is that the counselee initially has low learning motivation, where the counselee often does not participate in online learning and does not collect assignments given by the teacher. After the researcher carried out individual counseling services, there were positive changes that occurred to the counselee, namely the counselee had started to actively participate in online learning and always collected assignments given by the teacher. Changes that occur in counselees due to individual counseling activities carried out by researchers can be concluded that the role of individual counseling can be used to overcome the problems of students who are less motivated to learn in taking online learning during the Covid-19 pandemic.